2021
DOI: 10.1080/07853890.2021.2014556
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive overview of the venous disorder known as pelvic congestion syndrome

Abstract: Pelvic venous disorders (PeVD) also known as Pelvic Congestion Syndrome (PCS) affect a great number of women worldwide and often remain undiagnosed. Gynecological symptoms caused by vascular background demand a holistic approach for appropriate diagnosis. This is a relevant cause of chronic pelvic pain and atypical varicose veins. The diagnosis is based on imaging studies and their correlation with clinical presentation. Although the aetiology of PCS still remains unclear, it may result from a combination of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 126 publications
0
31
0
11
Order By: Relevance
“… 7 PCS typically presents with dyspareunia, dysmenorrhea, pelvic pain worsened by postural changes, and atypical VV (buttock, perineal, or vulval). 8 Concomitant NIVL has been described in up to 80% of patients. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 7 PCS typically presents with dyspareunia, dysmenorrhea, pelvic pain worsened by postural changes, and atypical VV (buttock, perineal, or vulval). 8 Concomitant NIVL has been described in up to 80% of patients. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic findings proposed by Coakley et al for cross-sectional imaging (both CT and MRI) include ≥ 4 ipsilateral parauterine veins of varying size, one of them showing >4 mm in diameter or the ovarian vein measuring > 8 mm. However, these cut-off diameters also differ between studies ( 4 , 6 , 30 , 31 ). Visualizing contrast medium flowing back from the left renal to the left ovarian vein on a CT scan is a common finding during the renal corticomedullary phase, seen in approximately 40% and often parous asymptomatic women ( 28 , 32 ).…”
Section: Role Of Imaging In Pevdmentioning
confidence: 91%
“…It is multifactorial; genetic predisposition, anatomical abnormalities, and hormonal factors notably contribute to the pathogenesis. Half of the pelvic varice cases are attributed to genetic factors and have a positive familial history ( 6 ). Furthermore, congenital absence or dysfunction of valves are described ( 7 ), as well as other aspects, including chronic dilatation of veins causing venous wall inflammation and leading to aggravated reflux ( 8 ).…”
Section: Pevd Pathophysiologymentioning
confidence: 99%
“…A recent British study found that the prevalence rate of CPP in women aged > 25 years was 14.8%, while the incidence rate was 20.5% in women of childbearing age and 9.6% in elderly females [ 5 ]. Recently, Balabuszek et al [ 6 ] showed that pelvic venous disorders (PeVD) might be the cause of CPP in up to 30% of women with CPP. CPP causes not only pelvic floor pain but also causes psychological distress and simultaneous negative behavioral and sexual consequences, resulting in depression, anxiety, poor sleep quality, and marital tension accompanied by pain.…”
Section: Introductionmentioning
confidence: 99%